1985
DOI: 10.1079/bjn19850087
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of ethanol on liver lipogenesis in the genetically-obese Zucker rat

Abstract: 1. Sixteen obese @/fa) Zucker rats, sixteen lean (Fa/-) Zucker rats and sixteen Wistar rats, all male rats aged 7-8 weeks, were given either a control (C) diet containing no ethanol or an ethanol (E) diet in which 36% of the energy was supplied by ethanol, for a period of 4 weeks.2. The activities of glucose-6-phosphate dehydrogenase (EC 1 . 1 . I .49), glucose-6-phosphatase (EC 3.1 .3.9) and glycerol kinase (EC 2 . 7 . 1 .30) and the glycogen content in the livers of obese (fa/fa) rats were lower in animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Possibly, we missed a rise in circulating lipids on an earlier time point. On the other hand, obesity has been shown to influence the turnover rate of circulating fatty acids and glycerol, and thus increased metabolization of these substrates by the liver could have decreased their serum concentrations . In our mouse study we indeed observed such signs of an elevated fatty acid and glycerol turnover rate in all obese mice, unaffected by nutrition or illness.…”
Section: Discussionmentioning
confidence: 53%
“…Possibly, we missed a rise in circulating lipids on an earlier time point. On the other hand, obesity has been shown to influence the turnover rate of circulating fatty acids and glycerol, and thus increased metabolization of these substrates by the liver could have decreased their serum concentrations . In our mouse study we indeed observed such signs of an elevated fatty acid and glycerol turnover rate in all obese mice, unaffected by nutrition or illness.…”
Section: Discussionmentioning
confidence: 53%
“…These include the role of Free Fatty Acids, FFA oxidation, reactive oxygen species, endoplasmic reticulum stress, genetics/epigenetics, the innate immune system, gut derived endotoxins, endogenous alcohol, intestinal dysbiosis and small intestinal bacterial overgrowth (SIBO). [193] Hepatic lipogenesis and fatty degeneration reduced in obese (fa/fa) rats given an ethanol diet showing a paradoxical effect of ethanol on liver lipogenesis in the genetically-obese Zucker rat Carmiel-Haggai et al, 2003 [194] Binge ethanol exposure increases liver injury in obese rats Olleros et al, 2008 [195] Moderately FAT diet and low-dose EtOH generate steatohepatitis and TNF liver expression. Changes in regulation of TNF associated with increased IL-6, IFN-gamma and iNOS expression.…”
Section: Nutritional Support In the Setting Of Alcohol Or Nicotine Usmentioning
confidence: 99%
“…The present results show that liver steatosis in the obese rats was less when diet E was given than when diet C was given. In a subsequent study (Karsenty et al 1985), an investigation of liver biochemical indices (glycogenesis, enzyme activities) led to the determination of one of the causes of this decrease: lowered hepatic lipogenesis activity in f a / f a rats eating diet E. The decrease in liver and adipose tissue lipogenesis and lipid synthesis is insufficient to affect the development of obesity and hyperlipidaemia, so these syndromes remain comparable for both diets.…”
Section: Hyperlipidaemia In the Fa/ Fa Zucker Rat After Alcohol Intoxmentioning
confidence: 99%